2014
DOI: 10.3892/mmr.2014.2411
|View full text |Cite
|
Sign up to set email alerts
|

HSP60 is involved in the neuroprotective effects of naloxone

Abstract: Heat shock protein (HSP)60 is primarily a mitochondrial protein. Previous experiments have found that changes in the location of intracellular HSP60 have been associated with apoptosis. Extracellular HSP60 mediates apoptosis via its ligand, Toll‑like receptor (TLR)-4. TLR-4 is an important factor expressed on microglia, with a central role in generating neuroimmune responses in the pathogenesis of neurodegenerative disorders. Naloxone is a highly effective nonselective opioid receptor antagonist, and has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
(34 reference statements)
2
23
0
1
Order By: Relevance
“…2C). HSF-1 is a transcription factor that regulates HSP60 expression and release (9). Western blot analysis revealed that the expression of HSF-1 was significantly upregulated by LPS compared with the control group; however, subsequent MT treatment significantly reduced this increase (both P<0.05; Fig.…”
Section: Hsp60 Expression Is Inhibited By Mt In Lps-stimulated Bv2 Cementioning
confidence: 89%
See 1 more Smart Citation
“…2C). HSF-1 is a transcription factor that regulates HSP60 expression and release (9). Western blot analysis revealed that the expression of HSF-1 was significantly upregulated by LPS compared with the control group; however, subsequent MT treatment significantly reduced this increase (both P<0.05; Fig.…”
Section: Hsp60 Expression Is Inhibited By Mt In Lps-stimulated Bv2 Cementioning
confidence: 89%
“…It has been demonstrated that HSP60 is highly expressed by activated microglia, and that the extracellular release of HSP60 increases the production of other proinflammatory factors through binding to toll-like receptor 4 (TLR-4) and stimulating neuronal cell death (8,9). Thus, the regulation of HSP60 production is a potential therapeutic option for the treatment of neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…(+)-Naloxone and related drug compounds have potential benefits over neutralising antibodies and other TLR4 antagonists. (+)-Naloxone potently blocks LPS-induced TLR4-mediated signaling in a variety of non-pregnancy models, suppressing NFκB activation and inhibiting TNF and IL1B induction in immune cells3435. As well as capacity to access and cross the placental barrier37, the established safety profile of closely related (−)-naloxone in pregnancy and infants is encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…(+)-Naloxone is a newly identified TLR4 antagonist that is the non-opioid isomer of the opioid receptor antagonist (−)-naloxone31, a well-described nonselective antagonist of the μ-opioid receptor commonly prescribed for opioid addiction, including in pregnant women and neonates32. (+)-Naloxone binds MD2 to prevent LPS engagement with TLR433 leading to diminished immune NFκB activation and IL1B, IL6 and TNF synthesis343536. In contrast to anti-TLR4 neutralizing antibodies24, (+)-naloxone is a small molecule which can penetrate across the placenta37, with a pharmacokinetic profile affording it short systemic exposure or longer term delivery if required.…”
mentioning
confidence: 99%
“…Flumazenil reduces the seizure threshold [70], and seizure activity is thought to be part of the injurious process after HI in neonates [71]. Midazolam and naloxone have also been shown to be neuroprotective in some rodent models of stroke [72,73]. Despite these potential effects, we chose to use the sedative drugs rather than the more commonly described halothane or isoflurane - which have also been described as potentially neuroprotective by providing a preconditioning effect [74] - as fentanyl and midazolam are also often used in human asphyxiated newborns and reproduce more accurately what the newborns are going through.…”
Section: Discussionmentioning
confidence: 99%